2020
DOI: 10.1016/j.bbrc.2020.05.217
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and validation of a drug-target microarray for SARS-CoV-2

Abstract: COVID-19 has become one of the worst epidemic in the world, currently already more than four million people have been infected, which probably co-exist with human beings, and has a significant impact on the global economy and political order. In the process of fighting against the epidemic in China, the clinical value of a variety of herbal medicines has been recognized and written into the clinical application guide. However, their effective molecular mechanism and potential targets are still not clear. Patho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Development of new experimental methodologies is also in progress, where Chen et al [47] constructed and validated SARS-CoV-2 drug target protein microarray and hypothesized it as a useful tool for pharmacological study. Khanit et al [48] demonstrated AGL-induced anti-SARS-CoV-2 activity using Calu-3-based anti-SARS-CoV-2 plaque assay, where the effectiveness of AGL in SARS-CoV-2-infected Calu-3 cells of lung epithelial tissues was determined and AGL application significantly inhibited the production of infectious virions (0.034 µM; IC50-0.036 µg/mL).…”
Section: Effectiveness Of Andrographolide (Agl) With New Emerging Viruses and Their Frequent Mutant Counterparts (Sars-cov-2 And Covid-19mentioning
confidence: 99%
“…Development of new experimental methodologies is also in progress, where Chen et al [47] constructed and validated SARS-CoV-2 drug target protein microarray and hypothesized it as a useful tool for pharmacological study. Khanit et al [48] demonstrated AGL-induced anti-SARS-CoV-2 activity using Calu-3-based anti-SARS-CoV-2 plaque assay, where the effectiveness of AGL in SARS-CoV-2-infected Calu-3 cells of lung epithelial tissues was determined and AGL application significantly inhibited the production of infectious virions (0.034 µM; IC50-0.036 µg/mL).…”
Section: Effectiveness Of Andrographolide (Agl) With New Emerging Viruses and Their Frequent Mutant Counterparts (Sars-cov-2 And Covid-19mentioning
confidence: 99%